Kebijakan Dana Dekonsentrasi: Tanggung Jawab Pemerintah Daerah Mewujudkan Pembangunan Kesehatan Nasional - Parko Prahima (Public Service and Governance Journal, 2022)
The health deconcentration fund is one of the funding schemes for regions in the context of delegating matters under the authority of the central government to regional governments in certain regions to support the achievement of national development. This research aims to analyze the policy for managing deconcentrated funds in the health sector in the region. This research uses qualitative methods with the Edward III policy implementation model. Data collection was carried out through interviews and documentation studies. The research results concluded that the implementation of deconcentrated fund management policies in the health sector in several regions in Indonesia is still not effective. This is caused by communication aspects that have not been maximized and the lack of adequate resource qualifications for managing deconcentration funds.